Confirmation of Host Genetic Determinants in the CFH Region and Susceptibility to Meningococcal Disease in a Central European Study Sample. Issue 10 (October 2015) - Biebl, Ariane; Muendlein, Axel; Kinz, Elena; Drexel, Heinz; Kabesch, Michael; Zenz, Werner; Elling, Roland; Müller, Christoph; Keil, Thomas; Lau, Susanne; Simma, Burkhard
<x xml:space="preserve">Abstract</x> Background: Invasive meningococcal disease (IMD) is a leading cause of meningitis and severe sepsis in children and adolescents. Genetic factors are important in determining the susceptibility to and outcome of IMD. Recently, a genome-wide association study from the United Kingdom showed significant associations of single-nucleotide polymorphisms within complement factor H (CFH; rs1065489) and in CFH-related protein 3 (rs426736) with susceptibility of IMD. We report data of a genetic replication study in Central European children. Methods: The study was conducted as a retrospective case-reference study involving 248 patients with confirmed diagnosis of IMD from Austria and Germany and 835 healthy reference individuals from a multicenter German birth cohort. Results: Carriers of the minor alleles of rs1065489 and rs426736 were at lower risk of IMD [allelic odds ratio = 0.60 (0.44–0.82); P = 0.001 and 0.61 (0.45–0.83); P = 0.001]. Also, 2 major haplotypes (GT and TC) derived from the 2 single-nucleotide polymorphisms were significantly associated with IMD (P = 0.001 and P = 0.003, respectively). Conclusions: The consistency of the results between the genome-wide association study and our study population strengthens the association of CFH polymorphisms to the susceptibility of IMD. Our results support the conclusion that CFH is a critical determinant in acquiring meningococcal disease.